Review: Mighty Be Our Powers: How Sisterhood, Prayer, and Sex Changed a Nation at War: A Memoir - Opeyeoluwa, Rotimi Olajide (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This book is very interesting, insightful, engaging, and hard to put down. It is also spicy, informative, and illuminating in all ramifications about the Liberian war, and her personal life and it unearths the hidden criminalities of war on vulnerable groups. The book is about the evolution of an individual and a nation at war; how a person, that is, the author fought her personal “wars” and translated the enormous strength she developed within the intervening years to confront the warlords bent on annihilating her nation and people. She dared the demons and prevailed but it was indeed not an easy assignment that life’s battles had equipped her for. The structure of the book is logical with a prologue and twenty-one-chapters, filled with gripping personal details and others stories related to the war of attrition that defined that epoch.